Proceedings of the 4th International Conference on Management, Economics and Business (ICMEB 2019) 2020
DOI: 10.2991/aebmr.k.200205.005
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Halal Food Knowledge to the Non-Muslim Consumers in Malaysia (Its Effect on Attitude and Purchase Intention)

Abstract: Health benefits become the main reason for the non-Muslim consumers to consume halal food. However, the non-Muslim consumers perceive that the Islamic slaughtering method is inhumane, at the same time. As a result, inconclusive findings are identified within the literatures leading to the need to address the gap of empirical evidence for the knowledge of the non-Muslim consumers towards halal food purchase intention. This study aims to fill this gap by investigating the relationship of Halal Food Knowledge (HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 58 publications
3
10
0
Order By: Relevance
“…(2009), Mukhtar and Butt (2011),;Bonne et al (2007),; Syed and Nazura (2011), Bashir et al (2019), Ariffin et al (2019), Aziz et al (2019), Wibowo et al (2020) and Rafiki and Wahab (2016).…”
Section: Effect Of Religiosity On Halal Productsmentioning
confidence: 99%
“…(2009), Mukhtar and Butt (2011),;Bonne et al (2007),; Syed and Nazura (2011), Bashir et al (2019), Ariffin et al (2019), Aziz et al (2019), Wibowo et al (2020) and Rafiki and Wahab (2016).…”
Section: Effect Of Religiosity On Halal Productsmentioning
confidence: 99%
“…A number of studies that have looked at halal foods have examined the influence of halal knowledge and purchase intention, but their studies have yielded inconsistent results. Elias et al (2016) and Khan et al (2022), for example, discovered that halal knowledge influences the intention to buy halal food, but Maichum et al (2017), Pratiwi (2018), and Wibowo et al (2020) found the opposite. Because of the contradictory results, further research is needed on the relationship between these two variables.…”
Section: Halal Knowledgementioning
confidence: 99%
“…This proves that Halal brands and products are no longer a regional practice but an international requirement to cater to the Islamic dietary sector (Stephenson, 2014), specifically in countries such as the UK and France. Meanwhile, there are many studies conducted on Halal products globally (Alam and Sayuti, 2011; Ariffin et al , 2019; Aziz et al , 2019; Bashir et al , 2019; Bonne et al , 2007; Lada et al , 2009; Mukhtar and Butt, 2011; Rafiki and Wahab, 2016; Wibowo et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%